Longitudinal predictors of reading comprehension in French at first grade: Unpacking the oral comprehension component of the simple view. (April 2019) - Massonnié, Jessica; Bianco, Maryse; Lima, Laurent; Bressoux, Pascal
Abstract: According to the simple view of reading (SVR), reading comprehension relies on "decoding" (pseudoword, word reading) and "oral comprehension" skills. Testing 556 French pupils, we aimed at unpacking these two components and tracking their longitudinal development in first grade. We have found that: (1) lower level language skills (vocabulary, syntax) and discourse skills (oral text comprehension) emerged as two dimensions of "oral comprehension"; (2) lower level language skills longitudinally predicted reading comprehension outcomes, above code-related skills; (3) decoding precursors (letter knowledge, naming speed and phonemic awareness) predicted reading comprehension directly, and indirectly, through decoding skills (pseudoword, word reading, text reading fluency); (4) Oral comprehension skills did not favour the development of decoding. Our results support the independency of the SVR components. However, we suggest that a more fine-grained conceptualisation of oral comprehension skills would help to better understand the individual and pedagogical factors influencing the early development of reading comprehension. Highlights: Oral comprehension skills uncover two dimensions of oral language. Lower level language (LLL) skills include vocabulary and syntax. Discourse skills reflect oral text comprehension. LLL skills longitudinally predict reading comprehension, above code-related skills. LLL skills and discourse skills do not longitudinally predict decoding skills.